A model for institutional phosphorus damage costs: A case study at the University of Virginia - Sy Coffey; Selina L. Cheng; Elizabeth Dukes; Geneviève S. Metson; Graham K. MacDonald; James N. Galloway (Environmental and Sustainability Indicators)
Calculating environmental “damage costs” associated with resource use can help individuals, communities, and institutions inform and improve their sustainability efforts. Though damage cost estimates have been developed for carbon and nitrogen, there is little precedent for calculating damage costs relating to phosphorus. We demonstrate a method to estimate institutional phosphorus damage costs using a case study of the University of Virginia, a public university in the United States. Our methods determine the source (diffuse agricultural and wastewater point source) and location (coastal and freshwater) of the University’s phosphorus footprint impacts, estimate the relative contribution of nitrogen and phosphorus across existing eutrophication damage costs, and then apply the results to the University’s phosphorus footprint. We found that activities at the University result in approximately $76 000 of annual downstream costs to society due to its phosphorus footprint ($2.08/kg of phosphorus released to the environment). About 48% of those damages are incurred in the Chesapeake Bay, which flows into the Atlantic Ocean and is the largest estuary in the United States, while 7% are incurred in the Gulf of Mexico. The remainder (45%) of costs are incurred in freshwater systems across both watersheds. Our findings are likely an underestimate of true societal impacts, as impacts such as losses of ecosystem services are difficult to value. However, we emphasize that this method is transferable and can be used by other institutions to calculate their phosphorus damage costs, providing a more holistic accounting of downstream environmental impacts.